2012
DOI: 10.1016/j.appet.2012.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Container size influences snack food intake independently of portion size

Abstract: a b s t r a c tWhile larger containers have been found to increase food intake, it is unclear whether this effect is driven by container size, portion size, or their combination, as these variables are usually confounded. The study was advertised as examining the effects of snack food consumption on information processing and participants were served M&M's for free consumption in individual cubicles while watching a TV show. Participants were served (1) a medium portion of M&M's in a small (n = 30) or (2) in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 26 publications
1
64
0
Order By: Relevance
“…Variables that have been shown to affect the portion of food selected, such as the size and shape of the container in which food is offered 17-20 or the bowl into which it is served, 21 were controlled in the present study. The same weight of cereal was presented in a large opaque container and differences between the cereals were not evident until the cereal was poured into a standard-size bowl.…”
Section: Resultsmentioning
confidence: 99%
“…Variables that have been shown to affect the portion of food selected, such as the size and shape of the container in which food is offered 17-20 or the bowl into which it is served, 21 were controlled in the present study. The same weight of cereal was presented in a large opaque container and differences between the cereals were not evident until the cereal was poured into a standard-size bowl.…”
Section: Resultsmentioning
confidence: 99%
“…Amount of food consumed was recorded in a wide variety of ways: grams (Marchiori et al 2012), ounces , kilojoules (Shah et al 2011), calories (Di Santis et al 2013), and "percentage of plate surface" . To avoid any confusion with energy intake (kilojoules), we only included amount consumed for foods that were homogenous in terms of energy density.…”
Section: Discussionmentioning
confidence: 99%
“…There is considerable evidence that smaller serving sizes significantly decrease consumption 410-413 . These studies have shown that the decrease in energy intake due to downsizing can often reach 30% change in calorie intake without generating within-meal calorie consumption 414 .…”
Section: Introductionmentioning
confidence: 99%